2019
DOI: 10.1007/s10640-019-00358-3
|View full text |Cite
|
Sign up to set email alerts
|

Using Individualised Choice Maps to Capture the Spatial Dimensions of Value Within Choice Experiments

Abstract: Understanding how the value of environmental goods and services is influenced by their location relative to where people live can help identify the economically optimal spatial distribution of conservation interventions across landscapes. However, capturing these spatial relationships within the confines of a stated preference study has proved challenging. We propose and implement a novel approach to incorporating space within the design and presentation of stated preference choice experiments (CE). Using an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…As our -and other studies' (e.g. Moran et al, 2007;Arriaza et al, 2008;Badura et al, 2019) results suggest, the European public supports policies that focuses on delivery of multiple public goods that agricultural lands can provide, such as landscape amenity, biodiversity protection, water and soil quality retention, and carbon sequestration. However, the majority of current CAP funding is made for mere land ownership rather than for delivery of such public goods.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…As our -and other studies' (e.g. Moran et al, 2007;Arriaza et al, 2008;Badura et al, 2019) results suggest, the European public supports policies that focuses on delivery of multiple public goods that agricultural lands can provide, such as landscape amenity, biodiversity protection, water and soil quality retention, and carbon sequestration. However, the majority of current CAP funding is made for mere land ownership rather than for delivery of such public goods.…”
Section: Discussionsupporting
confidence: 68%
“…These results may be country and/or context specific as some former studies revealed high relative welfare estimates for biodiversity and habitats (e.g. Christie and Rayment, 2012;Badura et al 2019), but not all (e.g. Liekens et al 2013).…”
Section: Aecm Budget Change Projections Accounting For National Funding Options and In Light Of Welfare Estimatesmentioning
confidence: 86%
See 1 more Smart Citation
“…Table 1 summarizes the review of ten articles from environmental economics. Only three of these include a scope discussion of the reported results (Layton and Brown 2000;Zhao et al 2013;Badura et al 2020). Four studies employ a restrictive functional form that imposes unitary scope elasticity (Adamowicz et al 1994;Zhao et al 2013;Meyerhoff et al 2016;and Ando et al 2020).…”
Section: Examples From Environmental Economicsmentioning
confidence: 99%
“…Within the choice modelling framework, spatial preference heterogeneity has been studied in four main ways: (i) using spatially explicit choice attributes; (ii) including spatial covariates in the choice model; (iii) applying geographically weighted (lagged) choice models; and (iv) developing a second-stage spatial analysis with individual-specific WTP estimates. The first approach uses spatially explicit choice cards or attributes that may impose an additional cognitive burden on the respondent (Badura et al, 2019;Brouwer et al, 2010;Horne et al, 2005;Johnston et al, 2002;Logar & Brouwer, 2018;Meyerhoff et al, 2014;Schaafsma et al, 2012). The second approach might increase the risk of potential multicollinearity and model overspecification by estimating the interaction effects of spatial covariates, such as respondent's location, distance to the environmental good and substitutes, or other spatial environmental data (Abildtrup et al, 2013;Bergmann et al, 2008;De Valck et al, 2014;Meyerhoff, 2013;Schaafsma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%